An analytical joint stiffness model for load transfer analysis in highly torqued multi-bolt composite joints with clearances. (1st November 2015) - Liu, Fengrui; Zhang, Jianyu; Zhao, Libin; Xin, An; Zhou, Longwei
Abstract: An analytical tri-linear joint stiffness model accounting for the effect of bolt-hole clearances on the bearing chord stiffness is presented. A single-parameter iteration method is also proposed to solve the nonlinear system of equations of the load transfer analysis, in which the recursive formulae are verified to be monotonic. To verify the present joint stiffness model, a series of single-lap, single-bolt joints with various bolt-hole clearances and bolt tightening torques were tested to empirically confirm the influence coefficients of the joint stiffness model. The load distributions in three single-lap, three-bolt joints with various clearances were also tested under finger-tight and highly torqued conditions. The load distributions in multi-bolt joints predicted by the presented joint stiffness model together with the single-parameter iteration method are in good agreement with the experimental outcomes, verifying the accuracy of the presented joint stiffness model and the feasibility of the single-parameter iteration method. In addition, the effects of the friction forces originated from the bolt-tightening torque and bolt-hole clearances on the load distribution in multi-bolt joints are presented.